E-093 Predictors of reperfusion and neurological outcomes for mechanical thrombectomy of anterior circulation large vessel occlusions: a multicenter study. (23rd July 2022) - Catapano, J; Naik, A; Koester, S; Stonnington, H; Rangel, I; Winkler, E; Srinivasan, V; Desai, S; Ducruet, A; Albuquerque, F; Jadhav, A
Abstract : Background: Mechanical thrombectomy is a mainstay in urgent management of ischemic stroke. Anterior circulation strokes compose of 80% of all strokes annually and are a great source of patient morbidity and mortality. In this study, we sought to identify predictors of post-MT reperfusion and neurological outcomes for anterior circulation MT. Methods: A retrospective analysis was performed on patients who underwent MT for an anterior circulation large vessel occlusion at two high-volume comprehensive stroke centers from 1/1/2020 to 6/30/2021. Institutional review board approval was obtained for this study. Demographic, patient presentation, procedural data and patient outcomes were abstracted from the medical record. The primary outcomes tested included the first pass effect (FPE) and modified FPE, which was defined as TICI ≥ 2C and 1 pass, and TICI ≥ 2B and 1 pass, respectively. Secondary outcomes included NIH Stroke Scale measurements at discharge and 24 hours. Multivariate analysis leveraged the firth's logistic regression for dichotomous outcomes and a Poisson regression for the continuous outcomes. Results: Two-hundred eighty-seven patients were identified: 48% were male and had a mean age of 69.52 (SD: 48.1). Mean ASPECT score at presentation was 8.98 (SD: 1.19). Approximately 90% of patients had good revascularization (TICI ≥ 2B) after thrombectomy. 73.2% of patients had occlusion of the middle coronary artery. Predictors of FPE included age, with each year adding 6% greater odds achieving FPE (p = 0.01), and the use of a stent retriever (OR = 0.24, 95% CI: 0.05 - 0.85, p = 0.025). Only stent retriever usage was found to be predictive of a mFPE (OR = 0.25, 95% CI: 0.09 - 0.55, p = 0.001). Predictors of discharge NIHSS were also obtained. ICA and M2/M3 occlusion, tandem occlusion, TPA usage, prehospital usage of anticoagulation or anti platelets, previous stroke or TIA history, diabetes, changing primary access due to initial failure, use of stent retriever, admission NIHSS, FPE were all found to be predictive of discharge NIHSS. FPE was also notable to be a significant predictor of 24-Hour NIHSS, along with admission NIHSS, initial blood pressure and use of stent retriever. Discussion: In this retrospective analysis of 287 patients, increasing age and no stent retriever used were predictors of FPE. While only the lack of stent retriever usage was predictive of mFPE. Additionally, demographic parameters and operative outcomes, such as FPE, have an impact on discharge neurological outcomes. These findings should be validated with more extensive controlled trials. Disclosures: J. Catapano: None. A. Naik: None. S. Koester: None. H. Stonnington: None. I. Rangel: None. E. Winkler: None. V. Srinivasan: None. S. Desai: None. A. Ducruet: None. F. Albuquerque: None. A. Jadhav: None.